Pengembangan Metode Imunokromatografi untuk Deteksi secara Serologi Campylobacter jejuni pada Ayam DEVELOPMENT OF IMMUNOCHROMATOGRAPHIC METHOD FOR DETECTING Campylobacter jejuni ON CHICKEN SEROLOGICALLY) - Rosyidi, Anwar; Budiharta, Setyawan; Asmara, Widya; Yudhabuntara, Doddi (Jurnal Veteriner; Vol 14 No 3 (2013), 2013)
Campylobacter spp cause infection in human in the form of gastroenteritis and Guillain-Barre syndrome.Campylobacter jejuni is one of  Campylobacter spp responsible for about 90% of cases of Campylobacteriosisin human with gastroenteritis.  Efforts to prevent the incidence of Campylobacteriosis in humans should bestarted with an assessment on its level of poultry. This study aims to develop a diagnostic test for C. jejunion chicken using immunochromatographic serological method. Stages of the research consist of thepreparation of test card, antigen preparation, optimization of the antigen and serum. The results showedthat immmunochromatographic card can distinguish infected serum from the uninfected.The minimumamount of antigen  was found to be 1,5 ng/µl. It needs 10 µl serum to perform the test properly.
Keywords: Campylobacter jejuni, immunochromatographic, village chicken